PERSEPSI MAHASISWA PGMI UIN AR-RANIRY TERHADAP SISTEM PEMBELAJARAN ONLINE PADA MASA AWAL PANDEMI COVID-19 - Khairatul ‘Ulya; Wati Oviana; Misbahul Jannah (PIONIR: JURNAL PENDIDIKAN, 2022)
Online study had been conducted in Islamic Elementary School Teacher Study Program (PGMI) at UIN Ar-Raniry far before the pandemic happened, the difference was the studying process was not entirely conducted online at that time. Therefore, this study aims to know the Islamic Elementary School Teacher Study Program (PGMI) student’s perception toward the online study system during Covid-19, the problem faced while the study process and the solution used to anticipate the obstacle during online study. This research used a qualitative descriptive method with a total 40 samples from purposive sampling technique. The data collection was conducted by questionnaire via google form and interviewed 15 participants to collect the detailed information. The result shows there are various perceptions from the participants toward online study and some arguments with a highest percentage, 100% students said that the internet connection was the common problem while 90% of students have difficulties in understanding online material. Those are the problems faced by PGMI students during the online study process. Besides, the students are still able to find a place with a better internet connection and learn independently. In conclusion, the online study process held during Covid-19 pandemic was not effective based on the student’s perception.